If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -6x + -9x = 99 Combine like terms: 6x + -6x = 0 0 + -9x = 99 -9x = 99 Solving -9x = 99 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-9'. x = -11 Simplifying x = -11
| 3*4*-2=x | | 3x^3+3x-6x=0 | | -6x-12=10+5x | | s(t)=-t^3+13t^2-40t | | 3c+4=11c | | -18=3(-a+6)+2z | | (7x^2-8)+(3x^2+1)= | | 13-4z=2z+9 | | 2x+2=-3x+6 | | 2x+2=4x+-6 | | cos(7x+ln(5x))=0 | | lx^2+3x+1l=1 | | 9-3x+2=10-3x | | 20+0.07(x-20)=0.06x | | 3u^2+3v^2-6uv+20u-20v+12=0 | | 1x-3y=14 | | Xy-4x+10=0 | | 9x+11=5x+1 | | 20+0.07x=0.06x | | x+9+2x=30 | | 11+2a=14 | | 3p=60+8p | | .2(x+100)=10 | | (-12)+6/2= | | 59-6x=3x+16 | | 20x+50b=320 | | -3x-y=17 | | 120+12x=545 | | 9x-2-4x-13=30 | | 4x^2-100x+625=0 | | x^2+20x+225=0 | | 4x-1=15x+1 |